Practical strategies for reducing ammonia volatilization from feedlots along Colorado's Front Range - Galles, Karen J., author; Ham, Jay M., advisor; Davis, J. G. (Jessica Gwyn), 1962-, committee member; Baron, Jill, committee member; Sharvelle, Sybil, committee member (Colorado State University. Libraries, 2011)
The Rocky Mountain National Park (RMNP) Initiative is a collaboration between state and federal agencies that has committed to achieving a 50% reduction (from 2004 levels) in N deposition in RMNP by 2032; current levels of N deposition have caused measureable changes in aquatic and terrestrial alpine ecosystems in the park. Northeastern Colorado, a region with a high concentration of livestock production, is likely one of the top two contributors to N deposition in RMNP. Reducing ammonia volatilization from Colorado's livestock sector will be important to achieving N deposition reduction goals in RMNP. To advance understanding of N loss from Colorado's feedlots, studies were done to examine: 1) the potential of reducing ammonia volatilization through lowering crude protein content in feedlot diets, 2) the effect of water sprinkling (a commonly prescribed dust control practice) on ammonia volatilization, and 3) the upper bound of ammonia flux from feedlot pen surfaces in Colorado. Two types of alternative feedlot diets - Oscillating N and Reduced N - were compared to a Control diet treatment and assessed for their effect on cattle performance and ammonia volatilization from pen surfaces. Intact pen surface samples were collected from November to March during a feeding trial from the three different diet treatments. Ammonia volatilization was measured under controlled conditions using a laboratory chamber system. The Reduced N diet (11.62% CP) significantly reduced cumulative 7-day ammonia emissions by 21 to 40% compared to the Control diet (13.5% CP). Average daily ammonia flux from Control diet samples ranged from 7.1 to 9.4 g NH3 m-2 d-1, while Reduced N diet samples had an average daily ammonia flux of 3.7 to 7.0 g NH3 m-2 d-1. There was no difference between the Oscillating N diet (11.62% CP 3 days/week and 13.5% CP 4 days/week) and the Control diet. Cattle performance (average daily gain) was not affected. A common feedlot practice to control dust and address frequent complaints from neighboring property owners and communities is to sprinkle the pen surface with water. Many feedlot operators have infrastructure in place - either solid set sprinklers on fencelines or water trucks that drive down the alleys - to sprinkle regularly during hot, dry conditions. The mechanics of ammonia volatilization suggest that watering could potentially increase N loss, but several studies suggest that water may have a suppressive effect on volatilization rates. Paired samples were taken from visibly obvious urine patches at a commercial feedlot in northeastern Colorado during July and August. In the laboratory, 5 mm of water - a typical amount of water applied for dust control - was applied to one sample from each pair, chosen randomly. Ammonia volatilization was then measured in a laboratory chamber system. Volatilization on the first day of measurement was 39.04 g NH3 m-2 d-1 for watered samples and 28.58 g NH3 m-2 d-1 for unwatered - a reduction of 27%. There was no difference in emissions on days 2 through 7 of measurement. This suggests that not only are N losses not exacerbated by this common dust control technique, but water application could be an effective co-BMP for reducing ammonia volatilization from the pen surface as well. By sampling urine patches during mid-summer very high ammonia fluxes (i.e. 50 g NH3 m-2 d-1) were captured that will be useful for parameterizing models for simulating patterns of ammonia losses from feedlots.
Keywords: ammonia fluxes; nitrogen transport; nitrogen deposition; livestock; beef feedlots